Exploration and Characterization of Flower Cabbage (Brassica oleracea Var. Botrytis) In Banuhampu District - Prana Dipa Tiarani; Nilla Kristina; Yusniwati Yusniwati (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Cauliflower (Brassica oleracea var. botrytis) is one of the vegetable commodities with high economic value. Cauliflower production in Indonesia reached 204,328 tonnes in 2020. This research was conducted from January to May 2022 in 3 sub-district in Banuhampu district. This study aimed to identify the morphological characters and growth diversity of cauliflower from Banuhampu district. The research method used is a survey method with purposive sampling consisting of two stages of activity, exploration and characterization. Morphological characterization was carried out on leaves and curds. The exploration has been carried out has succeed in characterizing 18 sampel of cauliflower which show narrow to broad phenotypic variability in the characters of leaves and curds, while the analysis of the level of similarity between samples obtained a coefficient value of 42 to 100%.